1998
DOI: 10.1128/jb.180.17.4332-4338.1998
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Biotransformation of Nonylphenol Polyethoxylates to Xenoestrogens in Pseudomonas putida

Abstract: A strain of Pseudomonas putida isolated from activated sewage grew aerobically on the xenoestrogen precursor, nonylphenol polyethoxylate (NPEO x , where x is the number of ethoxylate units) as sole carbon source. Comparative growth yields on NPEOav6, NPEOav9, and NPEOav20 (mixtures with average ethoxylate numbers as indicated) were consistent with utilization of all but two ethoxylate units, and the final accumulating metabolite was identified by gas chromatography-mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(41 citation statements)
references
References 38 publications
(41 reference statements)
2
33
0
3
Order By: Relevance
“…In this experiment, a stepwise ethoxyl chain shortening process from long-chain NPEOs to shorter chain polyethoxylates without the formation of related NPECs was observed, which suggested that NPEOs were biodegraded through a nonoxidative pathway. John & White (1998) proposed a hydroxyl shift mechanism for this nonoxidative ethoxyl chain removal process. According to the model, the hydroxyl shift leads to the formation of labile hemiacetal, which will subsequently release an acetaldehyde.…”
Section: Identification Of Biodegradation Intermediates and Biodegradmentioning
confidence: 99%
“…In this experiment, a stepwise ethoxyl chain shortening process from long-chain NPEOs to shorter chain polyethoxylates without the formation of related NPECs was observed, which suggested that NPEOs were biodegraded through a nonoxidative pathway. John & White (1998) proposed a hydroxyl shift mechanism for this nonoxidative ethoxyl chain removal process. According to the model, the hydroxyl shift leads to the formation of labile hemiacetal, which will subsequently release an acetaldehyde.…”
Section: Identification Of Biodegradation Intermediates and Biodegradmentioning
confidence: 99%
“…Because of their extensive use as detergents, emulsifiers, dispersing and wetting agents, non-ionic surfactants such as NPE are widely released in the environment, mostly after secondary biological treatment. As a consequence of biological wastewater treatment, partial degradation occurs with the formation of recalcitrant intermediates, which are considered important environmental pollutants attributed to their toxicity and endocrine disrupting activity (John and White, 1998;Ferguson et al ., 2001). As the primary source of these compounds is considered to be the breakdown of NPE during sewage treatment, many efforts were made to understand the fate of NPE in biological treatment (Gross et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Across the complete homolog distribution, a strong positive linear correlation (r 2 ϭ 0.96) occurred between ethoxylate chain length and K d for the organic-free sediment. For the longer homologs (NPEO [8][9][10][11][12] ), the K d values for the organic-free sediment were very similar to corresponding values for native sediment (within 95% confidence limits). However, at shorter chain lengths (NPEO 3-7 ) the values for the two sediments diverged markedly beyond 95% confidence limits, with the difference increasing with decreasing chain length.…”
Section: Adsorption From Mixturesmentioning
confidence: 66%
“…We have recently provided definitive evidence [12] that bacteria in pure culture achieve biodegradation of NPEO x by sequential removal of ethoxylate units from the terminus of the polyethylene glycol chain, that is, by sequential conversion of each component into its next lower homolog. In riverine environments, the additional presence of sediment particles will clearly have a marked impact on this process by differentially sequestering homologs of different chain lengths into the adsorbed state and thus restricting bioavailability to planktonic bacteria.…”
Section: Relevance Of Adsorption To Environmental Fatementioning
confidence: 99%
See 1 more Smart Citation